(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
Phraseological units, commonly referred to as idioms or fixed expressions, play a vital role in language. They are often seen as cultural gems that reflect the history, values, and norms of a given society. However, alongside their cultural specificity, many phraseological units exhibit intercontinental characteristics, transcending geographic and linguistic boundaries. This article explores the international nature of phraseological units, providing examples from various languages, including English, Spanish, French, and Russian, to illustrate their interconnectedness and shared meanings.